Mechanizmy regulace proteinové homeostázy ve vývoji nádorových onemocnění - Trčka, F; Müller, P; Vojtěšek, B (Klinicka onkologie, 2016)
BACKGROUND: The proteome of eukaryotic cells represents a complex system. Its components are exposed to various intrinsic and extrinsic stresses. Therefore, the function of the cellular proteome is dependent on the existence of compensatory mechanisms balancing the inner protein homeostasis - proteostasis. These mechanisms involve the network of molecular chaperones and transcriptional program regulating their expression. The process of cancerogenesis is accompanied by significant changes in the intracellular milieu of cancer cells - temperature, pH, availability of nutrients. On the one hand, these changes represent a consequence of the deregulated growth of the tumor tissue; on the other hand, they can be a source of selection pressure, which allows the emergence of resistant and aggressive tumor cell populations. Description of the proteostatic apparatus components and the mechanism of their involvement in the tumor tissue development is provided in this review article. AIM: This review focuses on the description of two causally linked groups of proteostatic events; their mutual coordination is crucial to the process of tumor cell and by extension the entire tumor tissue response to environmental and internal stress factors. The first group of these processes is represented by the "executory" role of molecular chaperones from HSP70, HSP90 and so-called small molecular chaperone protein families. These proteins are involved in maintaining stability of cellular proteins essential for proliferation, apoptosis, senescence, migration and phenotypic plasticity of tumor cells. The second group of the described processes comprises the posttranslational control of the "systemic" role of the transcription factor HSF1 in regulating the gene expression of molecular chaperones and other genes specifically regulated by this transcription factor in the tumor and stromal cells.Key words: molecular chaperones - heat-shock factor 1 - cancer - protein homeostasisThis work was supported by the project MEYS - NPS I - LO1413.The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study.The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Submitted: 15. 5. 2016Accepted: 25. 5. 2016.
Keywords: Heat-Shock Proteins; DNA-Binding Proteins; Neoplasm Proteins; molekulární chaperony; transkripční faktory tepelného šoku; nádorové proteiny; regulace genové exprese u nádorů; proteiny teplotního šoku; Transcription Factors; Neoplasms; transkripční faktory; Proteome; Humans; Gene Expression Regulation, Neoplastic; homeostáza; nádory; nádorová transformace buněk; DNA vazebné proteiny; proteom; Heat Shock Transcription Factors; Homeostasis; Molecular Chaperones; Cell Transformation, Neoplastic; lidé